Optimization of Multibrid Permanent-Magnet Wind Generator Systems - Li, Hui; Chen, Zhe; Polinder, Henk (IEEE transactions on energy conversion, 2009)
This paper investigates the cost-effective ranges of gearbox ratios and power ratings of multibrid permanent-magnet (PM) wind generator systems by using a design optimization method. First, the analytical model of a multibrid wind turbine concept consisting of a single-stage gearbox and a three-phase radial-flux PM synchronous generator with a back-to-back power converter is presented. The design optimization is adopted with a genetic algorithm for minimizing generator system cost. To demonstrate the effectiveness of the developed electromagnetic design model, the optimization results of a 500-kW direct-drive PM generator and a 1.5-MW multibrid PM generator with various gear ratios are, respectively, compared with those from other methods. Then, the optimal design approach is further employed for a range from 750 kW up to 10 MW. The optimization results of PM generator systems including direct-drive and multibrid wind turbine configurations are obtained, and the suitable ranges of gear ratios for different power ratings are investigated. Finally, the detailed comparisons of the most cost-effective multibrid PM generator system and the optimized direct-drive PM generator system are also presented and discussed. The comparative results have shown that the multibrid wind turbine concept appears more cost-effective than the direct-drive concept.